Moral dilemmas and moral theory - Mason, H. E. (Oxford University Press, 1996)
The essays in this work focus on the theoretical significance of moral dilemmas. The contributors, many of them philosophers who have shaped the current debate, shed light on standing controversies in moral philosophy.